2015
DOI: 10.1002/uog.14941
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic rate and accuracy of the ESHRE–ESGE classification for septate uterus and other common uterine malformations: why do we not see that the Emperor is naked?

Abstract: Diagnostic rate and accuracy of the ESHRE-ESGE classification for septate uterus and other common uterine malformations: why do we not see that the Emperor is naked?In our opinion, the results of the recent retrospective study of Graupera et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Revised interpretation of these studies' results using newly proposed cut-offs confirms that the reliability of measurements of internal indentation depth is significantly better than those of the indentation angle and the uterine wall thickness 23 . Moreover, the paradox of using an index based on the uterine wall (a variable parameter that is independent of deformity) for assessment of uterine cavity shape has been highlighted previously 35 : a small internal indentation may be recognized as septate uterus, and larger internal indentation as normal uterus depending on the uterine wall thickness 18,34,36 . Suggested cut-offs for uterine wall thickness by the study results (septate when I:WT > 110%) showed that I:WT can be accurate in diagnosis, but a wide margin of error for this benchmark (approximately ± 80% just by another observer repeating the measurement) indicates problems of its use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Revised interpretation of these studies' results using newly proposed cut-offs confirms that the reliability of measurements of internal indentation depth is significantly better than those of the indentation angle and the uterine wall thickness 23 . Moreover, the paradox of using an index based on the uterine wall (a variable parameter that is independent of deformity) for assessment of uterine cavity shape has been highlighted previously 35 : a small internal indentation may be recognized as septate uterus, and larger internal indentation as normal uterus depending on the uterine wall thickness 18,34,36 . Suggested cut-offs for uterine wall thickness by the study results (septate when I:WT > 110%) showed that I:WT can be accurate in diagnosis, but a wide margin of error for this benchmark (approximately ± 80% just by another observer repeating the measurement) indicates problems of its use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…5, available online) (45). This is an additional reason (beside the ESHRE-ESGE paradox: slight internal indentation may be recognized as a malformation, whereas a larger indentation may be recognized as a normal uterus depending on the uterine wall thickness) (46). The uterine wall thickness should not be a benchmark for the diagnosis of congenital uterine malformations (23,30,34).…”
Section: Discussionmentioning
confidence: 98%
“…However, the reliability and validity of this method need to be assessed in prospective studies. Whether the resulting images and volume measurements contribute to better understanding of uterine morphology and the relationship between uterine cavity volume, normal and abnormal uterine cavity shape and reproductive failure should be evaluated. Finally, refinement and testing of the newly proposed morphological indices for classification of uterine distortions (Figure ) should be performed.…”
Section: Techniquementioning
confidence: 99%
“…The availability of non‐invasive imaging techniques that allow evaluation of the uterus in the coronal plane, such as three‐dimensional (3D) ultrasound and magnetic resonance imaging, should improve diagnosis of uterine anomalies. However, current definitions for uterine morphology are controversial, which is a key limitation of studies evaluating the effectiveness of interventions for women with such conditions.…”
mentioning
confidence: 99%